2002
DOI: 10.1677/joe.0.1750435
|View full text |Cite
|
Sign up to set email alerts
|

Increased lactotrophs despite decreased somatotrophs in the dwarf (dw/dw) rat: a defect in the regulation of lactotroph/somatotroph cell fate?

Abstract: The dwarf (dw/dw) rat differs from all other rodent models of GH deficiency in that its pituitary prolactin (PRL) content is normal or even increased. We have now studied this throughout postnatal development, using a combination of immunocytochemistry, RIA and fluorescenceactivated cell sorting (FACS) and analysis. Compared with normal Albino Swiss (AS) rats, adult dw/dw rats showed a profound reduction in pituitary GH content accompanied by increased PRL content, significantly so in females (AS vs dw/dw; P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…These properties have been shown previously to reflect size and granularity, respectively, of cells isolated from the pituitary and other tissues [21,23]. Forward and side scatter profiling of AMCA + cells revealed three populations: small agranular cells (P1), larger agranular cells (P2), and large granular cells (P3; Fig.…”
Section: Further Enrichment Of Pcfcs By Physical Profiling Of Amca + supporting
confidence: 69%
“…These properties have been shown previously to reflect size and granularity, respectively, of cells isolated from the pituitary and other tissues [21,23]. Forward and side scatter profiling of AMCA + cells revealed three populations: small agranular cells (P1), larger agranular cells (P2), and large granular cells (P3; Fig.…”
Section: Further Enrichment Of Pcfcs By Physical Profiling Of Amca + supporting
confidence: 69%
“…With development, the cells spread to both lobes, and no difference between cell densities in the cephalic and caudal lobes was found. Bar 100 lm on results of morphological experiments on the differentiation of mammotropes have also been reported (Begeot et al 1984;Tierney et al 2002). They claimed that these contradictory results may be due to error in technique of double staining method or the used antibodies.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, the existence of somatomammotropes (SMTs), cells that produce both GH and Prl, and establishment of cell lines that produce both hormones are strong evidence for this transdifferentiation (Goluboff et al 1969;Frawley et al 1991;Inoue et al 1991;Chaidarun et al 1994). On the other hand, contrary results have cast doubt on the existence of SMTs and differentiation of somatotropes into mammotropes (Begeot et al 1984;Tierney et al 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Elevated levels of intracellular cAMP can inhibit the growth of some cell types but stimulate the growth of others. Among the cell types whose growth is stimulated by cAMP are thyroid [6], pituitary [7], and normal human breast epithelial cells in culture [8]. Several studies have demonstrated that cAMP inhibits the growth of established breast cancer cell lines and breast cancer cells in primary culture [8-10].…”
Section: Introductionmentioning
confidence: 99%